The Shogun age exhibition, from the Tokugawa Art Museum, Japan - Tokugawa Bijutsukan; Furuto, Kazuie (Tokyo : Shogun Age Exhibition Executive Committee, 1983)
Shogun age exhibition is being held in hopes of imparting a better understanding of Japanese history and traditional culture to the American and European people. This exhibition is mainly composed of articles used by the daimyo (such as swords, armor, household effects, and tea ceremony utensils), which have been handed down from generation to generation for more than tree hundred years within the Tokugawa family--the family that played a significant role in the pre-modern history of Japan. Approximately three hundred items have been carefully selected from the collection of the Tokugawa Art Museum in Nagoya for exhibition. Most of these valuable items have never been allowed out of Japan before, and the fact that they will be on exhibition in several cities in the United States and Europe for two and a half years is also unprecedented. The family of the Tokugawa shoguns exerted its authority in every aspect of Japan's pre-modern period as the supreme power in the land. In particular, the culture developed by the shogunal family was revered by the common people as the ideal culture of that time, and has been regarded as the source of traditional Japanese art. This catalog introduces all three hundred exhibit items in magnificent color photos, and with text that explains in readily understandable terms the significance fo the age of the shoguns, the authority wielded by the shogun, and the aesthetic sensiblilities fo the members of the samurai class.
Catalog of an exhibition held at Los Angeles County Museum of art, Dec. 17, 1983-Feb. 26, 1984, Dallas Museum of Art, Mar. 18-May 27, 1984, Haus der Kunst, Munich, Nov. 23, 1984-Feb. 3, 1985 and Espace Pierre Cardin, Paris, Mar 1-May 12, 1985.
Includes index.
Keywords: Tokugawa Bijutsukan -- Exhibitions; Art, Japanese -- Edo period, 1600-1868 -- Exhibitions; Art, Japanese -- Kamakura-Momoyama periods, 1185-1600 -- Exhibitions